2002
DOI: 10.1093/carcin/23.7.1243
|View full text |Cite
|
Sign up to set email alerts
|

Decreased gap junctional intercellular communication in hexachlorobenzene-induced gender-specific hepatic tumor formation in the rat

Abstract: Hexachlorobenzene (HCB), an epigenetic carcinogen, HCB induces the formation of liver tumors in female rats, whereas only a small percentage of males are responsive. Intercellular communication via gap junctions is decreased in carcinogenesis. Gap junctions are composed of proteins termed connexins (Cxs). The objectives of this study were (i) to determine if HCB-induced tumor development is associated with a loss of gap junctional communication; (ii) to assess if HCB causes a gender-specific decrease in the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 40 publications
1
15
0
2
Order By: Relevance
“…It could also affect cochlear neural elements. Indeed, it has been shown that, in the liver, HCB decreases gap junctional communication between cells by decreasing the production of connexin 32 and connexin 26 (Plante et al, 2002). However, all disturbances concerning connexins 26 and 30 in the cochlea induce deafness (DÕAndrea et al, 2002;Rabionet et al, 2002;Ahmad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could also affect cochlear neural elements. Indeed, it has been shown that, in the liver, HCB decreases gap junctional communication between cells by decreasing the production of connexin 32 and connexin 26 (Plante et al, 2002). However, all disturbances concerning connexins 26 and 30 in the cochlea induce deafness (DÕAndrea et al, 2002;Rabionet et al, 2002;Ahmad et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…HCB has also been demonstrated to induce liver tumors (Plante et al, 2002), renal adenomas , and parathyroid adenoma (Arnold et al, 1986) in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the low DDT dose group, mRNA expression and immunohistochemical staining of connexin 32 (Cx32) were found to be elevated 16 . Many previous studies indicated that high doses of DDT and other nongenotoxic carcinogens inhibit Cx32, resulting in the loss of the function of gap junction intracellular communication (GJIC) and release of potentially initiated cells from growth constraints imposed by normal neighboring cells, resulting in clonal expansion and ultimately tumor formation and progression [66][67][68][69][70] . In the present study, mRNA expression of one of the transcriptional factors, HNF-1α, which regulates Cx32 expression 71,72 , was in good correlation with that of Cx32 61 .…”
Section: Possibility Of a Hormesis For Hepatocarcinogenicity Of Ddtmentioning
confidence: 99%
“…The ozonation products of benzo( a )pyrene inhibit cell communication [28] and are believed to be carcinogenic [29]. It has been reported that chemicals such as dioxins, polychlorinated aromatic hydrocarbons, and cadmium, which can promote tumorigenesis, have been linked to decreased gap junctional intercellular communication in cultured hepatocytes [29–31]. Several oncogenes have also been reported as inhibiting GJIC [32].…”
Section: Discussionmentioning
confidence: 99%